The Role of Notaries in The Implementation of The Use of State Property After Regulation of The Minister of Finance No. 115 /PMK.06/2020 Concerning The Use of State-Owned Goods - Siti Aldlia Catur; Teddy Anggoro (IHSA Institute, 2022)
The regulations getting renewed and revised, Utilization asset related regulations also become the one that are treated the same periodically. The release of newest regulation related of the State Owned Goods Utilization, in this case The Provisions of Minister of Finance Regulation Number 115/PMK.06/2020 about State Owned Goods Utilization is a simplified version of all regulations related on State Owned Goods Utilization so far. This purpose of this research is to describe the state of notary deed in terms of cooperation Agreements of utilization which requires several number of State Owned Goods utilization which is done based on agreement made in the form of notarial deed. The type of this research is normative juridical, with the approach of the related laws and regulations to the legal issues that have been researched. This research shows that agreement utilization in the form of rental, cooperation utilization, Build Transfer operate/Build Operate Transfer, Cooperation of infrastructure Provisions (KSPI), and Limited Cooperation for Infrastructure funding, (Ketupi) requires a notary. Notarial deed in the implementation State Owned Goods Utilization agreement, after The Provisions of Minister of Finance Regulation Number 115/PMK.06/2020 about State Owned Goods Utilization released, becomes an authentic proofing tool. The role of notary becomes important in terms of agreement about state owned goods utilization.